Re-imagining the research process : conventional and alternative metaphors - Alvesson, Mats, 1956-; Sandberg, Jörgen (London : SAGE Publications Ltd, 2021)
This book offers a unique solution to the shortage of more imaginative and engaging research by re-imagining the core elements of the research process. In contrast to existing methods, which mainly focus on standard ingredients in the research process, the metaphorical approach taken here offers a more varied and comprehensive platform for producing novel, influential and relevant research. The set of guiding principles suggested in the book provides researchers with the resources to break away from existing conventions and templates for conducting and writing research. Re-imagining the Research Process: Conventional and Alternative Metaphors is suitable for upper-undergraduate and postgraduate students and researchers interested in challenging traditional views of the research process. Mats Alvesson holds a chair in the Business Administration department at Lund University in Sweden and is also a part-time professor at University of Queensland Business School, Australia and at Cass Business School, UK. Jorgen Sandberg is Professor at UQ Business School, University of Queensland, Australia, and Distinguished Research Environment Professor in Organization Studies at the Warwick Business School, UK.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Research -- Methodology